2022
DOI: 10.1039/d2cp02048c
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified C–H⋯O hydrogen bond in histidine

Abstract: Histidine C–H bonds observed in protein structures include (clockwise from top left): myoglobin, β-lactamase, and photoactive yellow protein; calculations indicate that tautomeric/protonation state influences H-bonding ability (bottom left).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…For histidine, the CH or NH of the imidazole ring can generally have a strong pi-interaction when facing the center of the benzene ring 70 , 71 . However, in the UBR4 UBR structure, the benzene rings of phenylalanine are perpendicular to the imidazole ring, indicating a relatively lower affinity than the others.…”
Section: Resultsmentioning
confidence: 99%
“…For histidine, the CH or NH of the imidazole ring can generally have a strong pi-interaction when facing the center of the benzene ring 70 , 71 . However, in the UBR4 UBR structure, the benzene rings of phenylalanine are perpendicular to the imidazole ring, indicating a relatively lower affinity than the others.…”
Section: Resultsmentioning
confidence: 99%
“…A survey of the structures obtained from both neutron and X-ray diffraction reveals a multitude of C-H. . .O interactions involving the imidazole ring [127,128] (e.g., Figure 5). Their strength suggests functional implications.…”
Section: Bonds Involving C-h Methine Groups In Hismentioning
confidence: 99%
“…A range of enzymes contains histidines within their active sites, and the C-H groups of imidazole are involved in various interactions. For example, in carbonic anhydrase, three histidines bind Zn 2+ , and the conformation of one is stabilized by a Cε-H acting as a donor to carboxyl of Glu106 [128]. No comprehensive survey of thefunctional roles of C-H…O bonds in enzymatic reactions has been published to date.…”
Section: Bonds Involving C-h Methine Groups In Hismentioning
confidence: 99%
“…For GH/Zn, we observed the greater broadening of 1623 cm -1 peak at 70 % RH, while AH/Zn spectra did not show appreciable change. [53][54][55] The signal at 1455 cm -1 due to carboxylate symmetric stretching also intensified with high RH. This finding led us to further explore the effects of RH on GH/Zn and AH/Zn nanofiber assemblies in the solid state.…”
mentioning
confidence: 95%
“…AFM also revealed that GH/Zn reorganized into spherical structures upon hydration, where directional hydrogen bonding is displaced by interactions with water-vapor in line with FT-IR data (Figure S20). 53,55 Using DFT calculations, we optimized water complexes featuring both GH/Zn and AH/Zn dimers, incorporating two water molecules inserted between the dimers which disrupt the intermolecular C=O•••H−N hydrogen bonds (Figure S35 in SI). The energy of formation (ΔEw) for these complexes and their corresponding enthalpy change (ΔHw) are as follows: ΔEw values are -17.7 and -17.0 kcal/mol, while ΔHw values are -13.9 and -12.9 kcal/mol (details in SI, Table S5), respectively.…”
mentioning
confidence: 99%